2009
DOI: 10.1258/td.2009.090039
|View full text |Cite
|
Sign up to set email alerts
|

Brucella endocarditis: a report from Iran

Abstract: Endocarditis is a rare focal complication of brucellosis but the most common cause of mortality. The diagnosis of the complications of endemic diseases is therefore important. We evaluated Brucella endocarditis cases in a teaching hospital in Iran between April 1998 and March 2006. Nine patients with a median age of 38.11 years were recorded, of whom seven (77.7%) were male. Underlying cardiopathy was present in three patients (33.3%). The median duration of the symptoms prior to diagnosis was 5.33 months. End… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Brucella endocarditis most commonly involves the aortic valve 6–8. The median duration of symptoms in such cases is reported to range from 3 to 5 months 6 8. In our case, the aortic valve was free of vegetation.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Brucella endocarditis most commonly involves the aortic valve 6–8. The median duration of symptoms in such cases is reported to range from 3 to 5 months 6 8. In our case, the aortic valve was free of vegetation.…”
Section: Discussionmentioning
confidence: 54%
“…Blood culture is the gold standard diagnostic test in diagnosis of brucellosis, but unfortunately it has a relatively low diagnostic yield. In a study by Esmailpour et al ,8 only 22.2% of cases with Brucella endocarditis had a positive blood culture. Therefore, various serological tests are now gaining diagnostic importance as they have a higher sensitivity 10 11…”
Section: Discussionmentioning
confidence: 89%
“…She was finally treated for Brucella endocarditis and osteomyelitis only with medical therapy. Previous similar studies on patients with BE showed that in the absence of a controlled trial, surgery should be part of the treatment and only medical therapy does not seem to be adequate in most cases (9). The current study patient had no cardiac failure and was treated with medical treatment.…”
Section: Discussionmentioning
confidence: 57%
“…Endocarditis is a rare complication, however, it is the most common form of cardiac involvement in brucellosis and major cause of death in these patients. The diagnosis of Brucella endocarditis is very difficult and requires strong clinical suspicion according to regional epidemiological pattern (5). In this case report, we share our experience on endocarditis and leukocytoclastic vasculitis as a rare skin involvement of brucellosis in children.…”
Section: Introductionmentioning
confidence: 75%